Modeling the effects of standardized ileal digestible isoleucine to lysine ratio on growth performance of nursery pigs(,) - Clark, A. B. (Transl Anim Sci, 2017)
Two experiments evaluated the effects of increasing standardized ileal digestible (SID) Ile:Lys ratio on growth performance of nursery pigs. In both experiments, dietary treatments consisted of 40, 44, 48, 52, 54, 58, or 63% SID Ile:Lys ratio. Diets were formulated using analyzed ingredient AA values and NRC (2012) SID coefficients. A combination of field peas and spray dried blood cells were used to ensure a low enough Ile diet concentration while minimizing the excess of Leu. The experiments consisted of 8 pens per dietary treatment with 5 pigs per pen for a total of 280 nursery pigs per experiment (Exp. 1: PIC 327 × 1,050, initially 6.7 ± 1.0 kg BW; Exp. 2: DNA 600 × 241, initially 6.0 ± 0.97 kg BW). Data were analyzed using mixed models with heterogeneous variance, where appropriate. The dose response was further characterized using quadratic polynomial (QP), broken-line linear (BLL), or broken-line quadratic (BLQ) functional forms. For Exp. 1, diets were initiated 6-d post-weaning and fed for 12-d followed by a common diet from d 12 to 28. From d 0 to 12, increasing dietary SID Ile:Lys ratio increased ADG (linear, P < 0.005) and ADFI (quadratic, P < 0.017) but G:F decreased (quadratic, P < 0.043). For ADG, the QP, BLL, and BLQ models resulted in maximum ADG at 64.7, 52.0, and 52.0 SID Ile:Lys ratios, respectively. For ADFI, the BLL breakpoint occurred at 50.6 and the QP predicted maximum ADFI at 56.2 SID Ile:Lys ratio. In Exp. 2, diets were initiated 6-d post-weaning for 7 pens and 3-d post-weaning for one heavier block and fed for 18-d followed by a common diet from d 18 to 32. From d 0 to 18, ADG and ADFI increased (quadratic, P < 0.016) with no evidence for difference in G:F as SID Ile:Lys ratio increased. For ADG, the QP and BLL had similar fit with breakpoints or maximums occurring at 58.3 and 51.8% SID Ile:Lys ratio, respectively. For ADFI, the BLQ breakpoint occurred at 52.0 SID Ile:Lys and the QP maximum ADFI at 57.2% SID Ile:Lys ratio. In conclusion, broken-line models reported maxima of 52.0% Ile:Lys ratio while quadratic models were as high as 64% of Lys to maximize ADG and ADFI of 6- to 11-kg nursery pigs. However, for the QP models 99% of the maximum response was achieved with a dose comparable to that from the broken line models. Therefore, these results are similar to the NRC (2012) requirement estimate of 51.1 Ile:Lys ratio.